2020
DOI: 10.1242/jcs.241752
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Met and voltage-gated Ca2+ channel signaling drives hypermigration of Toxoplasma-infected dendritic cells

Abstract: Ras-Erk MAPK signaling controls many of the principal pathways involved in metazoan cell motility, drives metastasis of multiple cancer types and is targeted in chemotherapy. However, its putative roles in immune cell functions or in infections have remained elusive. Here, using primary dendritic cells (DCs) in an infection model with the protozoan Toxoplasma gondii, we show that two pathways activated by infection converge on Ras-Erk MAPK signaling to promote migration of parasitized DCs. We report that signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…ERK1/2 phosphorylation increased transiently 1 h after infection by both strains and decreased afterwards. At later time points, however, infection by ME49 led to a gradually increased and sustained phosphorylation of ERK1/2, an observation in line with a recent study that reported a similar trend in bone marrow-derived dendritic cells infected with Prugniaud, another type II strain (Olafsson et al, 2020). Meanwhile, phospho-ERK1/2 levels in RH-infected cells remained low and comparable to basal levels seen in uninfected cultures.…”
Section: Discussionsupporting
confidence: 88%
“…ERK1/2 phosphorylation increased transiently 1 h after infection by both strains and decreased afterwards. At later time points, however, infection by ME49 led to a gradually increased and sustained phosphorylation of ERK1/2, an observation in line with a recent study that reported a similar trend in bone marrow-derived dendritic cells infected with Prugniaud, another type II strain (Olafsson et al, 2020). Meanwhile, phospho-ERK1/2 levels in RH-infected cells remained low and comparable to basal levels seen in uninfected cultures.…”
Section: Discussionsupporting
confidence: 88%
“…Their functions and experimental targeting approaches are detailed in the tabular representation, respectively. (6) Ca 2+ influx sets the cell in a hypermotile state by activation of MAP kinases and cytoskeletal rearrangements ( Ólafsson et al, 2020 ). In the tabular representation, ( a ) Red colored text indicates molecular components commonly expressed by mouse and human phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…When actively invaded by T. gondii, DCs undergo cytoskeletal changes with redistribution of integrins, reminiscent of MAT in ECM [24][25][26]. This migratory activation-termed hypermotility [27] requires live intracellular parasites [25], does not rely on chemotaxis [28] and is instead mediated by non-canonical GABAergic signalling and MAP kinase activation [23,[29][30][31][32]. However, it has remained unknown how highly migratory parasitised DCs interact with polarised endothelium.…”
Section: Introductionmentioning
confidence: 99%